PENGENALAN KOMUNIKASI PEMASARAN DI YAYASAN YATIM PIATU RASULULLAH SAW JAKARTA - Andrew, Richard; Piterson, Beatrice; Kurniawan, Alvira Nisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Rasulullah SAW Orphanage Foundation is one of many registered social institution in Jakarta. As one of the facilitator for orphans and homeless kids, the foundation tries to develop the children to save the future of the country. Leading for some innovations, the foundation had already digitized donation process far before the team arrived. However, the number of donations still sometimes not sufficient to help the student enroll normally. For example, they need the bag that not included from the local goverment social donation for education. Sometimes they also possesed excessive food stocks while they need other urgent equipments for the education process. Based on those problems, the CSR team from UNTAR try to develop their marketing communication skills by arranging the scheduled training session. The objective of the session is to develop the marketing communication skills for both the student and its foundation. As a result, both the student and the comittee from the foundation enthusiasticly participated the event. For the post-session expectations, they can enhance both their awareness and crowdfunding system by implementing a good marketing communication skills. The CSR team concluded that this program can work excellently if the foundation periodically develop their students’ skillsets by practicing the marketing communication techniques.